TEOLOGI KRISTEN SEBAGAI DASAR REFLEKSI IMAN DAN PRAKTIK KEHIDUPAN YANG MENEGUHKAN RELASI DENGAN ALLAH SERTA MEMPERKUAT SOLIDARITAS KEMANUSIAAN - Jefri Jefri; Windra Setiawan; Andros Teo Djorghi; Pelnium Tera Patandean; Evendi Trisael (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This article examines the relevance of Christian theology in addressing the challenges of modern life characterized by secularization, individualism, a technological ethical crisis, cultural pluralism, and environmental degradation. This research uses a qualitative method with a library study approach, through a critical analysis of Christian theological literature, church documents, and relevant academic works. The results of the study indicate that Christian theology not only has a doctrinal function but also a practical role in the daily lives of the people. Christian theology serves as a basis for faith reflection that strengthens the relationship with God, while strengthening human solidarity amidst the dynamics of modern society. In the face of secularization, Christian theology affirms faith as the center of the meaning of human life. In the face of individualism, theology emphasizes love and social solidarity. In the face of developments in science and technology, theology presents an ethical framework rooted in the word of God. Meanwhile, in the face of cultural and religious pluralism, Christian theology emphasizes the importance of open dialogue while remaining rooted in faith in Christ. Similarly, in the face of the environmental crisis, Christian theology encourages ecological spirituality as a manifestation of faith's responsibility. Thus, contextual, critical, and transformative Christian theology has proven relevant as a guide for the lives of people in building a more just, peaceful, and civilized world.